Kazakh prose of the early of ХХ century in the studies of Zinol Bisengali (Eurasian Journal of Philology Science and Education, 2021)
This article is devoted to the scientific activities of the doctor of philological sciences, professor, academician of the Shyngys Aitmatov International Academy of Social Sciences Zinol-Gabden Kabiuly Bisengali, who made an invaluable contribution to the study of Kazakh literature, the study of Kazakh prose of the early twentieth century. The relevance of scientific research lies in the analysis and identification of the features of the first samples of the prose genre, published in the press, in the study of the formation of the domestic prose genre at the beginning of the new century, in determining the patterns of its development, achievements and shortcomings. The article also examines the preconditions for the formation and development of professional prose and its unique originality, the connection between prose and the real life of the people. The author analyzes the unique methods and styles of individual writers, which Z. Bisengali explored in his scientific works. Particular attention is paid to an in-depth study of the formation of novel thinking in our literature. The article examines the artistic features of the Kazakh novel of the early twentieth century, analyzed in the studies of Zinol-Gabden Bisengali, studies in detail the thematic and worldview, artistic and stylistic studies of Kazakh writers, such as Sh. Kudaiberdyuly, M. Dulatov, S. Toraigyrov, Zh. Aymauytov, M Auezov, S. Seifullin, S. Mukanov and others. The article also presents the works of the scientist, revealing the peculiarities of thinking of Kazakh novelists of the early twentieth century and various factors that influenced their work.